Failure analysis of additively manufactured PLA with different morphological arrangements in erosive flow - Bilal Khan; Rehan Khan; Abdel-Hamid I. Mourad; Michał Wieczorowski; Asiful H. Seikh; Ibrahim A. Alnaser (Journal of Materials Research and Technology)
This study investigated the impact of water-sand slurry on Polylactic Acid (PLA) in Fused Deposition Modeling (FDM), exploring different morphologies and variables using Taguchi design. Variables included three designs (D1: Flat, D2: Groove, D3: Square groove), slurry concentrations (1%, 3%, 5% by weight), and impact angles (60°, 75°, 90°). Surface damage observed on PLA included cracks, micro-cutting, flakes, and craters due to erosion. The Groove design (D2) showed superior erosion resistance compared to Flat (D1) and square groove (D3). Analysis identified slurry concentration (64.68%) as the primary influencer of erosion, followed by design (23.80%) and impact angle (10.56%). These findings highlight the importance of optimizing FDM parameters to enhance PLA durability against abrasive conditions.